Environmental Constraints Mitigation Directly Drove the Diversifications of Fungal Community and Functional Profile in Amended Coastal Salt-Affected Soils - Yunlong Li; Weifeng Chen; Yiwei Xu; Jie Yu; Wengang Zuo; Yuhua Shan; Yanchao Bai (Agronomy)
Although organic amendment has been widely demonstrated to be capable of reassembling soil microbiomes in coastal salt-affected soils, quantitative characterization in respect to how abiotic and biotic components drive the diversifications of soil microbial community and function remains rudimentary. We investigated the effects of types and application rates of different exogenous organic ameliorants (sewage sludge, S; vermicompost, V) on the physicochemical properties, fungal community diversity, and fungal functional traits in coastal salt-affected soils. Results revealed that both S and V amendments exhibited significantly positive impacts on the alleviation of environmental constraints and the reassembly of fungal community and functional profile. Of note, efficacy of the two exogenous organic ameliorants was significantly influenced by the types of carbon sources utilized and the rates at which they are applied. More pronounced variations in soil physicochemical and microbiological properties were observed in soils amended by S and V at the application rate of 200 t ha−1. Both S and V treatments positively boosted soil fungal community diversification with higher compositional diversities found in the majority of amended soils when compared to unamended soils. In addition, S and V applications favored the flourishment of functions linked to saprotrophic strategy with soil saprotrophs and wood saprotrophs predominating the functional profiles in soils amended by S and V, respectively. Results obtained from redundancy analysis and structural equation modeling revealed that pH, salinity, and SOC were the principle edaphic factors that significantly and directly affected the reassembly of fungal community. In addition, fluctuations in the prevalence of specific fungal genera, including Stachybotrys, Trichoderma, Mortierella, and Acremonium, emerged as a decisive biotic factor influencing diversifications of fungal communities and functional profiles. Taken together, this study not only highlighted the efficacy of S and V application on environmental constraints alleviation in coastal mudflats, but also qualitatively identified and quantitatively illustrated potential pathways and effectiveness of edaphic and biotic components driving the diversification of soil fungal microbiomes and functional profiles. These findings would enhance our understanding in respect to the microbial-mediated amelioration process of salt-affected soils within coastal mudflat ecosystem.